HYDROPONIC VEGETABLE MARKETING STRATEGY IN PALU CITY INDONESIA - Shintami R Malik; Sulmi Sulmi; Husnul Khatima; Lien Damayanti; Rustam Abd Rauf (Universitas Tadulako, 2021)
Hydroponics is plant cultivation that utilizes water media without using soil. The hydroponic vegetable products produced are diverse, ranging from kale, bok choy, mustard greens, and lettuce. This study aimed to identify internal and external factors that influence marketing and identify marketing strategies for hydroponic vegetables in Palu City. The results showed that the evaluation of the internal and external factors showed that the strength factor had a score of 1.85, the weakness factor was 1.26, the opportunity factor was 1.74, and the threat factor was 1.16. Thus, the highest score was achieved by internal factors (strength) of 1.85, and the lowest was the weakness of 1.16. Hydroponic vegetable marketing in Palu City is in the SO Strategy. In this condition, it has great power and great opportunities to market.